The Development of Radio Republik Indonesia (RRI) Palembang Branch 2000-2015 (Material Contribution to the VII Indonesian National History Course) - Rita Yuliani; Farida Farida; Yunani Yunani (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2018)
This research has titled “the development of Radio Republik Indonesia (RRI) branch of Palembang in 2000-2015 (material contribution in the national histori of Indonesia VII). This study aims to determine the development of radio Republik Indonesia branch Palembang in the field of organization. To know the role of radio Republik Indonesia branch Palembangand the development of radio Republik Indonesia Palembang branch in the field of quality improvement of broadcasting. The method used in reseacrh is the historical method through heuristic stages, source criticism dividen into external criticism and internal critic, interpretation and historiography, and using sociological approach and political approach. The result of this research explains the development of radio Republik Indonesia and programa owned radio Republik Indonesia, explaining the role of radio Republik Indonesia branch of Palembang and efforts made to improve the quality of radio broadcasting Republik Indonesi branch Palembang based on the results of this knowins that the radio Republik Indonesia branch Palembang has function research as a medium used to get information, preserve the culture and media that has a role in improving the quality of education.